2021
DOI: 10.3389/fpsyg.2021.789793
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the German Version of the Demoralization Scale-II and the Association Between Demoralization, Sociodemographic, Disease- and Treatment-Related Factors in Patients With Cancer

Abstract: Objective: To test the psychometric properties, internal consistency, dimensional structure, and convergent validity of the German version of the Demoralization Scale-II (DS-II), and to examine the association between demoralization, sociodemographic, disease- and treatment-related variables in patients with cancer.Methods: We recruited adult patients with cancer at a Psychosocial Counseling Center and at oncological wards. Participants completed the 16-item DS-II, Patient Health Questionnaire-9 (PHQ-9), Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 60 publications
(141 reference statements)
4
41
1
Order By: Relevance
“…(2016, b) reported α = 0.89 for the whole scale [20], and it was α = 0.93 in the study by Koranyi et al [19]. It…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…(2016, b) reported α = 0.89 for the whole scale [20], and it was α = 0.93 in the study by Koranyi et al [19]. It…”
Section: Discussionmentioning
confidence: 87%
“…Originally introduced DS-II as a re ned measure of demoralization consisting of 16 items and 2 subscales: Meaning and Purpose and Distress and Coping Ability [20]. Koranyi et al (2021) used Con rmatory Factor Analyses to evaluate whether the proposed two-factor solution of the original DS-II scale [20] can be replicated with their sample of patients with cancer. They tested Two models: the one-factor model, aggregating across all 16 items, and the two-factor model according to the dimensional structure of two proposed subscales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,28,31,34 Two studies reported lower levels of demoralization in patients with shorter time since diagnosis, 44,46 but four studies reported that time since diagnosis was not associated with demoralization. 19,20,29,35 One study reported lower levels of demoralization in cancer patients who had radiotherapy, 28 but one study reported that radiotherapy was not associated with demoralization. 33 Five studies concluded that symptom burden was a positive predictor of demoralization, 17,18,30,37,43 but one study suggested that symptom burden was not significantly related to demoralization.…”
Section: Resultsmentioning
confidence: 99%
“…There was conflicting evidence for the relationship between the sociodemographic factors of age, gender, education, marital status, religion, employment status, monthly income, number of children, and demoralization. There was some evidence that cancer patients who were young, 28,29 single, [30][31][32] female, 30,32 unemployed, 32,33 and had low monthly income 31,32,34,35 have a higher probability of experiencing demoralization. Patients with at least one child 36 and those with religious beliefs 37 were less likely to experience demoralization.…”
Section: Factors Associated With Demoralizationmentioning
confidence: 99%